Clinical features of a novel TIMP-3 mutation causing Sorsby's fundus dystrophy: implications for disease mechanism. Issue 12 (1st December 2001) - Clarke, Michael; Mitchell, Keith W; Goodship, Judith; McDonnell, Sharon; Barker, Michael D; Griffiths, Ian D; McKie, Norman
Abstract : AIMS: To describe the phenotype in three family members affected by a novel mutation in the gene coding for the enzyme tissue inhibitor of metalloproteinase-3 (TIMP-3). METHODS: Three members of the same family were seen with a history of nyctalopia and visual loss due to maculopathy. Clinical features were consistent with Sorsby's fundus dystrophy. Exon 5 of the gene coding for TIMP-3 was amplified by the polymerase chain reaction, single strand conformation polymorphism analysis undertaken and exon 5 amplicons were directly sequenced. RESULTS: Onset of symptoms was in the third to fourth decade. Five of six eyes had geographic macular atrophy rather than neovascularisation as a cause for central visual loss. Peripheral retinal pigmentary disturbances were present. Scotopic ERGs were abnormal in all three. Mutation analysis showed a G→T transversion in all three resulting in a premature termination codon, E139X, deleting most of the carboxy terminal domain of TIMP-3. CONCLUSIONS: The patients described had a form of Sorsby's fundus dystrophy which fell at the severe end of the spectrum of this disease. Postulated disease mechanisms include deposition of dimerised TIMP-3 protein.